2011
DOI: 10.1371/journal.pone.0023322
|View full text |Cite
|
Sign up to set email alerts
|

Snail Involves in the Transforming Growth Factor β1-Mediated Epithelial-Mesenchymal Transition of Retinal Pigment Epithelial Cells

Abstract: BackgroundThe proliferation of retinal pigment epithelium (RPE) cells resulting from an epithelial-mesenchymal transition (EMT) plays a key role in proliferative vitreoretinopathy (PVR), which leads to complex retinal detachment and the loss of vision. Genes of Snail family encode the zinc finger transcription factors that have been reported to be essential in EMT during embryonic development and cancer metastasis. However, the function of Snail in RPE cells undergoing EMT is largely unknown.Principal Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 42 publications
7
90
0
2
Order By: Relevance
“…[27][28][29][30] However, most in vitro studies used exogenously applied TGFb to activate cellular pathways leading to EMT. 24,[31][32][33] Assays conducted in the current study were performed without addition of exogenous TGFb, yet the cells were able to respond to wounding by activating EMT. The three TGFb isoforms encoded by the human genome 34 have distinct and overlapping functions during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] However, most in vitro studies used exogenously applied TGFb to activate cellular pathways leading to EMT. 24,[31][32][33] Assays conducted in the current study were performed without addition of exogenous TGFb, yet the cells were able to respond to wounding by activating EMT. The three TGFb isoforms encoded by the human genome 34 have distinct and overlapping functions during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…15 In support of our results, several reports demonstrated that Snail knockdown reverts TGF-b-induced EMT and cell migration in cancer cells. 17,25 TGF-b signals have been suggested to cross talk with estrogenic signal pathways during the tumorigenesis and development of cancers. 2,13 Our present study revealed for the first time that TGF-b treatment can increase the expression and nuclear translocation of ERRa in osteosarcoma cells, while not affect other molecules including ERa, ERb, and ERRg.…”
Section: Erra Is Involved In Tfg-b Induced Transcription Of Snail In mentioning
confidence: 99%
“…Snail, a negative regulator of E-cadherin, is one of the key transcription factors promoting EMT (32). Furthermore, the mesenchymal markers MMP9 and α-SMA have been particularly associated with tumor progression and metastatic dissemination in different human cancers (33,34). Here, we demonstrated that GPC3 promoted tumor metastasis through the induction of EMT and could potentially be used as a biomarker.…”
Section: Discussionmentioning
confidence: 79%